Case report: Efficacy of later-line fam-trastuzumab deruxtecan in a patient with triple-positive breast cancer with brain metastases - Sumou, Ingrid Karmane; Hui, Cheng Vai (Frontiers in Oncology, 2024)
Fam-trastuzumab deruxtecan (T-DXd) has demonstrated substantial antitumor activity and durable responses in patients with human epidermal growth factor receptor 2 positive (HER2+) metastatic breast cancer. We report here the treatment outcomes of T-DXd in a patient with HER2+ breast cancer with brain metastases that repeatedly recurred and progressed after two lines of salvage therapy. In 2016, a 23-year-old G0P0 female with risk factors including menarche at age 9 years, Li-Fraumeni syndrome, and a strong family history of cancer was diagnosed with bilateral, triple-positive breast cancer. She received chemotherapy, HER2-targeted therapies, total mastectomy, and locoregional radiotherapy, but a brain metastasis in the left parieto-occipital lobe was detected in 2020. After receiving capecitabine, lapatinib, gonadotropin-releasing hormone (GnRH) agonist, and tamoxifen, multiple new lesions appeared in the brain after 14 months. The patient then received capecitabine, neratinib, GnRH agonist, and letrozole; however, her brain metastases still progressed after 7 months. In 2022, she started T-DXd treatment. Good response to treatment was observed 4 months later, including a continuous decrease in the cancer antigen 15-3 level, a reduction in the size of the major brain tumor, and the absence of new lesions. Now aged 30, the patient is continuing to receive T-DXd treatment to prevent recurrence. We conclude that T-DXd was effective for the treatment of brain metastases in this young patient with triple-positive metastatic breast cancer who had multiple risk factors and had received several anti-HER2 therapies prior to T-DXd.